2005
DOI: 10.1523/jneurosci.4000-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Calcium Ion and Membrane Potential Transients Follow the Pattern of Epileptiform Discharges in Hippocampal Slice Cultures

Abstract: Emerging evidence suggests that mitochondrial dysfunction contributes to the pathophysiology of epilepsy. Recurrent mitochondrial Ca 2ϩ ion load during seizures might act on mitochondrial membrane potential (⌬⌿m) and proton motive force. By using electrophysiology and confocal laser-scanning microscopy, we investigated the effects of epileptiform activity, as induced by low-Mg ] m fluctuated during interictal activity in single dendrites, and these fluctuations spread over the entire mitochondrial compartment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
85
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 68 publications
4
85
1
Order By: Relevance
“…Calcium uniporter was inhibited using Ru360. 6,26 Ru360 with actions specific to mCU activity is known to always reduce mitochondrial Ca 2 þ uptake in various cell types, 6,[27][28][29] leading to decreased or unchanged overall cytoplasmic Ca 2 þ transients during stimulation 13,30 and in some cases increased overall cytoplasmic Ca 2 þ . 6 Calcium uniporter activity was enhanced using Kaempferol, a compound known to increase mitochondrial and overall cytoplasmic Ca 2 þ levels.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium uniporter was inhibited using Ru360. 6,26 Ru360 with actions specific to mCU activity is known to always reduce mitochondrial Ca 2 þ uptake in various cell types, 6,[27][28][29] leading to decreased or unchanged overall cytoplasmic Ca 2 þ transients during stimulation 13,30 and in some cases increased overall cytoplasmic Ca 2 þ . 6 Calcium uniporter activity was enhanced using Kaempferol, a compound known to increase mitochondrial and overall cytoplasmic Ca 2 þ levels.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore mitochondria-specific Ca 2+ indicators (rhod-2) have been used in combination with mitochondria specific markers, such as MitoTracker® Green, to differentiate between mitochondrial and cytosolic rhod-2 fluorescence (Kovacs et al, 2005). The co-localization of both dyes studied by alternating excitation at 488 and 543 nm with a confocal microscope revealed that the dotted rhod-2 fluorescence is colocalized with MitoTracker® Green, and represents intramitochondrial Ca 2+ .…”
mentioning
confidence: 99%
“…This approach, in combination with high resolution imaging techniques such as confocal or two-photon microscopy, allows monitoring of mitochondrial Ca 2+ transients at subcellular levels. For example, using rhod-2 or a lower Ca 2+ binding affinity variant rhod-ff (K d 570 nM and K d 19 μM respectively), it was possible to distinguish within CA3 pyramidal neurons a heterogeneous population of mitochondria, which displays different degrees of Ca 2+ uptake during epileptic activity (Kovacs et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This study, performed in chondrocytes following a mechanical insult, is also the first to show that dantrolene (RyR inhibitor) is able to prevent mitochondrial depolarization. Ru360 (a uniport transporter inhibitor) has been reported to inhibit mitochondrial depolarization in neurons (69). Much work is still needed to determine the role of these channels in chondrocytes subjected to physiologic mechanical stimulation.…”
mentioning
confidence: 99%